Promoting sustainability through national transport planning - Barfod, Michael Bruhn; Leleur, Steen; Gudmundsson, Henrik; Hedegaard Sørensen, Claus; Greve, Carsten (European Journal of Transport and Infrastructure Research, 2018)
This following special issue of the European Journal of Transport Infrastructure Research (EJTIR) containing 4 scientific papers is the result of the work conducted under the research project ‘National Transport Planning – Sustainability, Institutions and Tools’ (SUSTAIN) (2012- 2017) financed by the Danish Innovation Fund. SUSTAIN was coordinated by first the Department of Transport of the Technical University of Denmark (DTU Transport) and later as the result of a reorganisation of the transport research at DTU by the Department of Management Engineering (DTU Management Engineering). The project was carried out in cooperation with several Danish and international partners. In SUSTAIN the following definition of national sustainable transport planning (NSTP) was adopted: deliberate, knowledge-based, and strategic endeavours to integrate sustainability principles, criteria and goals in the development, management, regulation and assessment of nationally significant transport systems and services. This paper presents the research outcome by reviewing some of the major findings and seeing these collectively as a basis for promoting sustainability through the formulated research topic of NSTP. This basis includes defining criteria and indicators for use in NSTP combining evidence-based and performance oriented planning approaches. Furthermore, it contains a flexible evaluation framework that includes a decision support model that when informed by criteria and indicators can structure and assist an NSTP practice. This practice can support a planning process aiming at realising a sustainable transport development. Finally, the basis comprises a review of the complex political and administrative fabric in which NSTP is embedded, and thereby it can condition the ability to promote sustainability in practice.